Impact of neoadjuvant chemotherapy on survival prognosis and pathological downstaging in patients presenting with high-risk upper tract urothelial carcinoma: A protocol for systematic review and meta analysis. Issue 18 (May 2020) - Li, Kun; Xie, Wenjie; Gao, Liang; Huang, Gaomin; Zhou, Jiaming; Mei, Baoyu; Chen, Jie
Abstract: Purpose: Controversy remains with using neoadjuvant chemotherapy (NAC) in patients with upper tract urothelial carcinoma (UTUC). Thus, we conducted a systematic review and meta-analysis of the peer-reviewed literature to assess the role of NAC in high-risk UTUC patients. Methods: PubMed, EMBASE, and the Cochrane Library were the main sources of relevant studies. The search terms included: "Upper urothelial carcinoma"; "UTUC"; "Urinary tract cancer"; and "Transitional cell carcinoma" combined with "Neoadjuvant chemotherapy" and "adjuvant chemotherapy". We studied the relationship of UTUC and NAC. Overall survival, recurrent-free survival, cancer-specific survival and pathological response rate in patients treated with/without NAC before radical surgery were evaluated. Results: Five trials were selected, and included 532 participants. Each of the included studies was retrospective. The combined analysis showed that when compared to controls, the pooled hazard ratios of overall survival, recurrence-free survival and cancer-specific survival were 0.47 (95% confidence interval [CI], 0.34–0.64; P  < .00001); 0.50 (95% CI, 0.37–0.66; P  < .00001); and 0.37 (95% CI, 0.25–0.54; P  < .00001), respectively. It indicates the beneficial effects of NAC for the prognosis of survival in UTUC. Additionally, NAC was significantly associated with T-stage down-grading (T3/4 to ⩽T2; OR=7.58 [4.66, 12.33]; P  < .0001) and pathological lymph node status (N+ to N0; OR = 6.24 [2.57, 15.15]; P  < .00001). Conclusions: NAC treatment before radical nephron-ureterectomy significantly improves survival prognosis in patients with high-risk upper tract urothelial carcinoma. However, considerable prospective and randomized studies are needed to confirm this perspective.